Performance of barley (Hordeum vulgare L.) varieties in relation to sowing dates and row spacing in central Punjab - Ram, Hari; Kaur, Harvinder (Journal of Cereal Research, 2018)
Two field experiments were conducted at the research farm of the Punjab Agricultural University, Ludhiana. The soil of the experimental field was low in organic carbon content and slightly alkaline in nature. One experiment was conducted in two dates (Timely and late sown) in main plot and four barley varieties (DWRUB 52, DWRB 101, BH 902 and RD 2849) in sub-plot during 2014-15 and 2015-16. Another experiment was conducted on row spacing (20.0, 22.5 and 25.0 cm) as main plot and three barley varieties (BH 902, BH 946 and RD 2552) in sub-plot during 2015-16 and 2016-17. Timely sown (15th-19th November) barley recorded higher grain yield than late sown (December 15). Varieties DWRUB 52 and DWRB 101 performed better than BH 902 and RD 2849 under different sowing dates. The grain yield recorded in 22.5 cm row spacing was better than 20.0 cm but similar to 25.0 cm row spacing. The variety BH 946 recorded higher grain yield than BH 902 and RD 2552 in different row spacing. Â Doi.org/ 10.25174/2249-4065/2018/83630